2015
DOI: 10.1371/journal.pone.0137606
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Characteristics and Treatment Outcomes of Children Selected for Treatment of Severe Acute Malnutrition Using Mid Upper Arm Circumference and/or Weight-for-Height Z-Score

Abstract: ObjectivesDebate for a greater role of mid-upper arm circumference (MUAC) measures in nutritional programming continues, but a shift from therapeutic feeding programs admitting children using MUAC and/or weight-for-height Z (WHZ) to a new model admitting children using MUAC only remains complicated by limited information regarding the clinical profile and response to treatment of children selected by MUAC vs. WHZ. To broaden our understanding of how children identified for therapeutic feeding by MUAC and/or WH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 21 publications
4
30
0
Order By: Relevance
“…Thus, the present data suggest that the two indicators are complementary and additive rather than alternative measures that compete to identify the same individual children at increased risk of death. This is supported by the observation that children with both a deficit in MUAC and WHZ have a worse prognosis that those with a single anthropometric deficit [16]; furthermore addition of other deficits such as a low height-for-age or weight-forage progressively increase the risk of death confirming the additive effect of such deficits [39].…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Thus, the present data suggest that the two indicators are complementary and additive rather than alternative measures that compete to identify the same individual children at increased risk of death. This is supported by the observation that children with both a deficit in MUAC and WHZ have a worse prognosis that those with a single anthropometric deficit [16]; furthermore addition of other deficits such as a low height-for-age or weight-forage progressively increase the risk of death confirming the additive effect of such deficits [39].…”
Section: Discussionmentioning
confidence: 75%
“…These analyses show that MUAC has a better sensitivity and specificity than WHZ in predicting subsequent all-cause mortality of the individual child [37]. There are other cogent reasons for favouring MUAC such as its ease of use in the community [16]. However, both low MUAC and low WHZ are associated with an increased risk of subsequent death; albeit at least half the deaths are not related to anthropometric status [1,16,38] and deaths due to accidents such as drowning are more likely in active well-nourished children.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Grellety et al [12] published a study from Sudan indicating that MUAC only identified more severely malnourished children with a higher risk of mortality but failed to identify a third of the children who died. A study by Isanaka et al [13] investigated differences in children identified for therapeutic feeding by MUAC and/or WHT in terms of demographic, anthropometric, clinical, and laboratory and treatment response characteristics and found that using MUAC only identified younger and more female children but did not well differentiate children in terms of other measures of nutritional vulnerability. There are also clear population differences, highlighted by Dasgupta et al [14] in their study when using either MUAC and WHT in India.…”
Section: Study Findings and Implicationmentioning
confidence: 99%